Digital Banking for Empowerment: How Technology Shapes the Financial Behavior of Millennials - Kurniawan, Novan; Satyarini, Yuane; Sukresna, I Made; Mahfudz (LifeSciFi, 2025)
This study investigates the impact of digital banking on the financial behavior of millennials. Utilizing a literature review methodology, the research compiles and analyzes findings from various studies exploring the relationship between digital banking services and millennials' financial management practices. The results indicate that digital banking significantly enhances accessibility to financial services, encouraging millennials to engage more actively in budgeting, saving, and investing. Furthermore, factors such as convenience, security, and financial literacy play critical roles in the adoption of these technologies. The contribution of this research lies in providing valuable insights for financial institutions to tailor products and services that meet the needs of the younger generation, while emphasizing the importance of financial education to maximize the benefits of digital banking.